Immunoglobulins and predicted mortality in clinical course of concomitant HIV and TB infection - N. V. Mal’tseva (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
A search for prognostic markers of HIV and tuberculosis coinfection (HIV/TB), especially in case of Mycobacterium tuberculosis multidrug resistance (MDR MBT) associated with low rates of TB eradication, is of relevance in connection with the problem of choosing adequate anti-TB therapy which is able to decrease mortality. 113 HIV/TB patients aged 24 to 58 years were examined: 70 males and 43 females hospitalized at the Novokuznetsk TB Clinic during the 2017—2019 period. MDR MBT (concomitant resistance to Isoniazid and Rifampicin) was found in 50 patients (12 patients with MDR MBT had additional resistance to Fluoroquinolones) aged 24 to 54 years — 31 males and 19 females. The control group consisted of 49 healthy individuals aged 27 to 72 years (26 females and 23 males) lacking focal and systemic infections with moderately pronounced age-related changes. In plasma samples, concentration of total (non-specific) immunoglobulins of classes E, M, G, A (including secretory immunoglobulin A, sIgA) were measured by using enzyme-linked immunosorbent assay. Data statistical processing was performed by using licensed software packages InStatII, Microsoft Excel, IBM SPSS Statistics 22. An extended range of individual variability in count of peripheral blood CD4 lymphocytes was revealed both among non-survivor and survivor patients with HIV/TB examined, being a drawback of using such parameter as lethality predictor. It was found that the serum level of total IgE, IgM, IgG, IgA and sIgA in patients with HIV/ TB was higher than that one in control group, whereas in non-survivor vs. survivor patients the concentration of IgE and sIgA was elevated. The coefficient of disease outcome prediction (CP) for patients with HIV/TB and MDR MBT was calculated being equal to the ratio of the multiplication of serum concentration of IgE, IgM, IgA and secretory IgA to CD4 lymphocyte count (CP = IgE x IgM x IgA x sIgA/CD4). CP higher than 200 was detected in 77% non-survivor and 6% of survivor patients. The relative risk of death with CP > 200 was very high (OR = 56.7, p < 0.0001) being 8.5 times higher than that one upon CD4 < 200 (OR = 6.7, p = 0.0237). A positive correlation between CP and lethal outcome was more valuable than that of CD4. The data presented allow us to propose CP for clinical use as an effective prognostic criterion for HIV/TB with MDR MBT.